2004
DOI: 10.1128/aac.48.10.3823-3827.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Pharmacokinetics and Pharmacodynamics of Itraconazole and 14-Hydroxyitraconazole at Steady State

Abstract: Itraconazole (ITRA) is a triazole antifungal agent that has been used successfully for the treatment of aspergillosis, candidiasis, coccidioidomycosis, blastomycosis, cryptococcosis, and histoplasmosis (7,10,13,25,32,35,39,40). The recommended oral and intravenous dose in adults is 200 mg once or twice daily. Bioavailability is approximately 55% after administration of the oral solution. At steady state, the maximum concentration of drug in serum (C max ), time to C max , minimum concentration of drug in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
(81 reference statements)
2
27
0
2
Order By: Relevance
“…The conversion of itraconazole to an active metabolite, hydroxy-itraconazole, has also been confirmed in humans (8,9). The antifungal titer obtained in our results suggested that the pharmacodynamic activity of the metabolite was comparable to that of itraconazole in mice as well as humans (4,13,23,31). The parent compound and its active metabolite would shared in vivo activities against C. albicans and A. fumigatus in mice.…”
Section: Discussionsupporting
confidence: 58%
“…The conversion of itraconazole to an active metabolite, hydroxy-itraconazole, has also been confirmed in humans (8,9). The antifungal titer obtained in our results suggested that the pharmacodynamic activity of the metabolite was comparable to that of itraconazole in mice as well as humans (4,13,23,31). The parent compound and its active metabolite would shared in vivo activities against C. albicans and A. fumigatus in mice.…”
Section: Discussionsupporting
confidence: 58%
“…Fluconazole also readily penetrates the extracellular space of the rat lung (fluid/plasma concentration ratio of 1.38), and this is unaffected by inflammation (138). Itraconazole exhibits ELF exposures that are one-third of the plasma AUC in human volunteers, while the AUC in alveolar cells is more than double that of the plasma (56). In postmortem samples from four hematology patients, the mean lung tissue/plasma concentration ratio of itraconazole was 7 (139), while Heykants and colleagues (73) reported concentrations 0.9 to 2.4 times higher than those in the plasmas of four patients.…”
Section: Lungmentioning
confidence: 99%
“…For this reason, it may be more useful to present the tissue area under the concentrationtime curve (AUC) for comparison. There are few studies that do this for humans (56,57,58,59,60,61,62), and with one exception (59), all deal with pulmonary distribution. Most of the antifungal agents considered in this review do exhibit hysteresis.…”
Section: Limitations Of Current Understanding and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Con itraconazol y tras la administración oral de 200 mg cada 12 h en dosis múl-tiple, se observaron resultados similares que incluyen concentraciones elevadas dentro de las células alveolares [7].…”
Section: Características Farmacocinéticasunclassified